Analisis Lanjut Pemanfaatan Empiris Ramuan Seledri (Apium graveolens L) oleh Penyehat Tradisional - Handayani, Lestari; Widowati, Lucie (Jurnal Kefarmasian Indonesia, 2020)
Celery (Apium graveolens L) is a very popular plant as a soup and many other vegetable menus. Celery has benefits as a medicinal plant and the efficacy has been known worlwide. Research on Medicinal Plants and Herbs (Ristoja) conducted in 2012, 2015, and 2017 has collected thousands of herbs and some of them contain celery. This study carried out further analysis on the empirical use of celery as an ingredient of traditional medicine by traditional healers (Hattra) through interviews and observations. Based on Ristoja's data, they found 90 herbs and among them there were 20 local names of herbs which are used by Hattra. The celery by Hattra was empirically identified for 10 types of diseases treatment. It was used mostly for hypertension or high blood pressure treatment and justificatied scientifically through other scientific literatures. It was recommended that celery could be use for self-medication a mild hypertension patient. Celery was safe although there are still contra indications. The celery treatment should be socialized through promotive activities in elderly posyandu activities remain under supervision of health workers